Applications of Neural Networks in Advanced Oxidative Process - Silva, Messias Borges; Guimarães, Oswaldo Luiz Cobra; Siqueira, Adriano Francisco; Filho, Hélcio José Izário; Filho, Darcy Nunes Villela; Aquino, Henrique Otávio Queiroz de; Oliveira, Ivy dos Santos; Almeida, Carlos Roberto de Oliveira (IntechOpen, 2011)
None